Insemination Capability of Male Pteromalus Venustus (Hymenoptera: Pteromalidae), a Gregarious Parasitoid of Megachile Rotundata (Hymenoptera: Megachilidae) - V. J. Tepedino (Psyche: A Journal of Entomology)
Inseminative ability in Pteromalus venusus, an arrhenotokous parasitoid presumed to have evolved under Local Mate Competition, was studied by recording the progeny production of a series of six virgin females presented to males at hourly intervals. Most males did not reach the upper limits of their inseminative abilities: Three-quarters of the males inseminated at least four females, twice the ratio of females-to-males in an average brood (2:1). There was no evidence of sperm depletion: The few uninseminated females did not tend to be those presented later in the mating sequence, and a comparison of progeny production by female position in the mating sequence showed no tendency for females presented later to produce fewer females than those presented earlier. The data suggest that males can inseminate at least twice the number of females that normally share a host with them. The breeding system of this species may be moving towards panmixis because of recent selection pressures caused by domestication of its primary host, the alfalfa leafcutting bee.